2011
DOI: 10.1007/s11703-010-1056-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of alginate oligosaccharides on growth, yield and alkaloid production of opium poppy (Papaver somniferum L.)

Abstract: Opium poppy (Papaver somniferum L.), an important medicinal plant, produces several opiate alkaloids including morphine, thebaine, codeine, papaverine and noscapine. Polysaccharides, such as sodium alginate, have been used in depolymerized form as wonderful promoters of plant growth. The present study has revealed that application of alginate oligosaccharides (AO), obtained from sodium alginate irradiated by Co-60 gamma rays, significantly enhances certain physiological/biochemical parameters as well as the ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
30
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 23 publications
9
30
0
1
Order By: Relevance
“…In this regard, irradiated SA appears to facilitate the efficient absorption and utilization of mineral nutrients [26,27]. Similar enhancement in leaf N, P and K contents due to irradiated SA application to various other crops has been reported by [26][27][28][29]. They applied various concentrations of irradiated SA on the leaves of Papaver somniferum L. and reported that irradiated SA at 120 ppm concentration improved leaf-nitrogen content to the maximum.…”
Section: Papia Haque Etal(2017) Effect Of Gamma Irradiated Sodium Asupporting
confidence: 56%
See 2 more Smart Citations
“…In this regard, irradiated SA appears to facilitate the efficient absorption and utilization of mineral nutrients [26,27]. Similar enhancement in leaf N, P and K contents due to irradiated SA application to various other crops has been reported by [26][27][28][29]. They applied various concentrations of irradiated SA on the leaves of Papaver somniferum L. and reported that irradiated SA at 120 ppm concentration improved leaf-nitrogen content to the maximum.…”
Section: Papia Haque Etal(2017) Effect Of Gamma Irradiated Sodium Asupporting
confidence: 56%
“…A promotive effect of irradiated SA on chlorophyll content might perhaps be attributed to the irradiated SA increased leaf-N that is a constituent of chlorophyll molecule. Irradiated SA also increased the total chlorophyll and carotenoids contents in the leaves of fennel [28] , opium poppy [29] , and beetroot [27,30] .…”
Section: Papia Haque Etal(2017) Effect Of Gamma Irradiated Sodium Amentioning
confidence: 99%
See 1 more Smart Citation
“…Increases in lateral root formation (Vernieri et al 2005), total root volume (Slávik 2005;Mancuso et al 2006), and root length (Zodape et al 2011) have been observed and attributed to the presence of phytohormones such as auxins and cytokinins in seaweed extracts (Khan et al 2011a(Khan et al , 2011b. Seaweed extract application also stimulated mineral nutrient uptake in plants such as lettuce (Crouch et al 1990), grape (Mancuso et al 2006), soybean (Rathore et al 2009), tomato (Zodape et al 2011), and winter rapeseed (Jannin et al 2013) with increased accumulation of both macro-(N, P, K, Ca, S) and micro-nutrients (Mg, Zn, Mn, Fe) reported (Crouch et al 1990, Mancuso et al 2006, Rathore et al 2009Zodape et al 2011).…”
Section: Specific Effects Of Seaweed Extracts On Plantsmentioning
confidence: 99%
“…Seaweed extracts contain a variety of plant hormones including cytokinins, auxins, abscisic acid, gibberellic acid and salicylic acid determined indirectly by bioassays (reviewed by Khan et al 2009 andCraigie 2011;Khan et al 2011b) and directly by methods such as high pressure liquid chromatography (HPLC), gas chromatography-mass spectrometry (GC-MS), and liquid chromatography-mass spectrometry (LC-MS) (Stirk et al 2003;Gupta et al 2011). Cytokinins and cytokinin-like compounds are the most widely reported in seaweed extracts, followed by auxins and auxin-like compounds (Stirk et al 2003;Khan et al 2009;Craigie 2011), and these have often been speculated to be responsible for the plant growth enhancing effects of the extracts (Khan et al 2009;Craigie 2011).…”
Section: Plant Hormonesmentioning
confidence: 99%